2013
DOI: 10.1186/1472-6963-13-357
|View full text |Cite
|
Sign up to set email alerts
|

Players and processes behind the national health insurance scheme: a case study of Uganda

Abstract: BackgroundUganda is the last East African country to adopt a National Health Insurance Scheme (NHIS). To lessen the inequitable burden of healthcare spending, health financing reform has focused on the establishment of national health insurance. The objective of this research is to depict how stakeholders and their power and interests have shaped the process of agenda setting and policy formulation for Uganda’s proposed NHIS. The study provides a contextual analysis of the development of NHIS policy within the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
74
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(76 citation statements)
references
References 19 publications
2
74
0
Order By: Relevance
“…Mubyazi and Gonzalez-Block (8) documented a case of malaria treatment change in Tanzania where the decision to change the first anti-malarial drug given high resistance levels was protracted, characterized by the MoH commissioning more studies to gather more evidence on different aspects of the policy change and implementation including cost, implementation feasibility and community acceptability. Similarly Basaza et al (23) documented a case of designing a health insurance scheme in Uganda emphasizing the need for comprehensive evidence encompassing financial feasibility, political acceptability, popular support, impact on employment and private sector growth to guide decision-making. This emphasizes the need for evidence informing different aspects of decision-making and policy implementation.…”
Section: Discussionmentioning
confidence: 99%
“…Mubyazi and Gonzalez-Block (8) documented a case of malaria treatment change in Tanzania where the decision to change the first anti-malarial drug given high resistance levels was protracted, characterized by the MoH commissioning more studies to gather more evidence on different aspects of the policy change and implementation including cost, implementation feasibility and community acceptability. Similarly Basaza et al (23) documented a case of designing a health insurance scheme in Uganda emphasizing the need for comprehensive evidence encompassing financial feasibility, political acceptability, popular support, impact on employment and private sector growth to guide decision-making. This emphasizes the need for evidence informing different aspects of decision-making and policy implementation.…”
Section: Discussionmentioning
confidence: 99%
“…There exists limited evidence on how policymakers take account of contextual issues. At a national level, a stable political system has a positive impact on policy development (Basaza, O'Connell, & Chapcakova, ; Mbachu et al, ) where the converse was found to hinder policy development (El‐Jardali, Bou‐Karroum, Ataya, El‐Ghali, & Hammoud, ). Health policymaking must sit comfortably within the wider national health strategic framework which can either act as a roadmap for policymaking or constrain attempts at policy reform (Mc Hugh, Perry, Bradley, & Brugha, ; Onwujekwe et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…A push for policy reform has also come from within healthcare professions (Archer, Regan de Bere, Nunn, Clark, & Corrigan, ). This includes the need to implement standards from regulation agencies (Blaauw et al, ) or because of health system restructuring and reform (Basaza et al, ; Mc Hugh et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations